Adeno-associated virus vectors transduce primary cells much less efficiently than immortalized cells. - Halbert, C L (1995)
Immortalized cell lines have been used to study infection and replication of adeno-associated virus (AAV) in culture, but primary cells presumably provide a better model for AAV behavior in animals. Here, we have evaluated the ability of AAV vectors to transduce primary and immortalized strains of human epithelial cells and fibroblasts. Two AAV vectors were used, one that transduced an alkaline phosphatase gene (AAV-LAPSN), and one that transduced a beta-galactosidase/neomycin phosphotransferase fusion gene (AAV-L beta geo). The transduction efficiency of the AAV-LAPSN vector, quantitated by measurement of alkaline phosphatase-positive cell foci following infection, was 10 to 60 times greater in immortalized human cells than in primary cells, and total alkaline phosphatase activity in cell lysates was 40 to 50 times greater in immortalized cells. The AAV-L beta geo vector gave similar results. In contrast, the transduction efficiency of a retrovirus vector encoding alkaline phosphatase was equivalent in primary and immortalized cells. Analysis of the quantity and state of the AAV vector genomes in cells showed that primary and immortalized cells contained comparable numbers of vector copies per cell and that the vast majority of vector DNA was not integrated into the cell genome. Additionally, the level of AAV vector-derived message paralleled the transduction efficiency. These results indicate that the block to functional transduction in primary cells occurred after virus entry and limited the abundance of vector-derived message. Data from AAV transduction in cultures of human cells containing immortalizing genes suggest that cellular changes secondary to the introduction of immortalizing genes increased permissiveness for transduction by AAV vectors. In summary, our data demonstrate that AAV vectors transduce primary human cells much less efficiently than immortalized cells and indicate the importance of using primary cells to evaluate AAV vectors for gene therapy applications.